Can Tetrylone Act in a Similar Fashion to Tetrylene in Ni(CO)2 Complexes? A Theoretical Study based on a Comparison using DFT Calculations. Issue 13 (30th May 2017) - Nguyen, Thi Ai Nhung; Tran, Duc Sy; Huynh, Thi Phuong Loan; Le, Thi Hoa; Duong, Tuan Quang; Nguyen, Tien Trung; Vo, Thanh Cong; Pham, Van Tat; Dang, Tan Hiep
Abstract : A comparison was made to investigate the structures and bonding of nickel complex that carry tetrylone and tetrylene ligands [(CO)2 Ni‐{E(PH3 )2 }] (Ni1E ) and [(CO)2 Ni‐NHEMe ] (Ni2E ) (E = C to Pb) using quantum chemical calculations at the BP86 level with various basis sets (SVP, TZVPP, TZ2P+). The nature of the Ni–E bonds was analyzed with charge‐ and energy decomposition methods. The structures of tetrylone complexesNi1E exhibit an interesting trend with the ligands E(PH3 )2 are bonded in a tilted orientation relative to the fragment Ni(CO)2 . In contrast, the calculated equilibrium structures of complexesNi2E exhibit the NHEMe ligands (E = C to Sn) bonded in a head‐on way to the Ni(CO)2 fragment, while the bending angle gives the strongest side‐on bonded ligand NHPbMe when E = Pb. The interesting trend of the bond dissociation energy (BDE) is observed for the tetrylone, which has the same trend BDEs compared with tetrylene complexes. The EDA‐NOCV results indicate that the tetrylone ligands {E(PH3 )2 } in complexes are similar to the tetrylene ligands NHEMe as strong σ‐donors and weak π‐acceptors. The BDEs calculated for the Ni–E bonds inNi1E andNi2E show that the effect of bulky ligands may obscure the intrinsic Ni–E bond strength. The bonding analysis shows that the tetrylone ligands inNi1E may act in a similar fashion to the tetrylene ligands inNi2E . All complexesNi1E andNi2E are suitable targets for synthesis. Abstract :